PERSEPSI RESPONDEN TERHADAP CITRA PERUSAHAAN YANG DIBANGUN MELALUI KEGIATAN CORPORATE SOCIAL RESPONSIBILITY PADA BANK JATENG CABANG SURAKARTA - SUGIJADI SUGIJADI (JURNAL WIDYA GANECWARA, 2014)
The aim of this study were: (1) To identify the categories of CSR Central Java Bank in Surakarta. (2) To analyze the factors that affect the imaging Central Java Bank in Surakarta through CSR activities. (3) To know the most important factor in imaging Central Java Bank in Surakarta CSR activities This research takes an object on Central Java Bank in Surakarta, with research subjects CSR program participants in the Central Java Bank Surakarta, the number of samples taken were 96 respondents. The sampling technique using random sampling method. The data collection method using a questionnaire, questionnaires, and observations with data analysis techniques using indices and chi-square analysis. The results of the analysis it was found that there is a positive relationship between corporate identity, reputation, service oferring, physical environtment, and personal contact with the company's image on Central Java Bank in Surakarta. The results of calculation of the index of consumer attitudes are at a good reception area. Based on the results of factor analysis service offering the ultimate in imaging Central Java Bank in Surakarta through CSR activities. This can be seen from the value of X2 is equal to 1.042541, followed by personal contact, corporate identity, physical environtment and reputation.